Biodiversity and Host–Parasite (Co)Extinction - van Dijk, Jeroen; de Baets, Kenneth (The Evolution and Fossil Record of Parasitism, 2021)
Parasitism is one of the most common modes of life, and yet it is often disregarded or ignored in nature conservation. We are at the brink of the sixth mass extinction and in order to assess the extinction risk of both parasites and their hosts, we first need to fully understand the role and function of parasites in ecosystems. Parasites might play an active role in their host’s extinction, and coextinction has been postulated to be the most common mode of extinction. However, parasites may be able to survive their host’s extinction through host switching, perhaps to a more abundant host, for example. The dilution effect has been described as an important natural defense mechanism for the host: higher biodiversity is associated with lower infection risk. Discussed here is the importance of biodiversity and host–parasite associations and (co)extinction, and the role the fossil record has in filling the knowledge gap regarding deep-time host–parasite interactions.
Keywords: Biodiversity; Co-extinction; Dilution effect; Host–parasite associations; Fossil record; Host switching

Extinction risk controlled by interaction of long-term and short-term climate change - Mathes, Gregor; van Dijk, Jeroen; Kießling, Wolfgang; Steinbauer, Manuel J. (Nature Ecology & Evolution, 2021)
Assessing extinction risk from climate drivers is a major goal of conservation science. Few studies, however, include a long-term perspective of climate change. Without explicit integration, such long-term temperature trends and their interactions with short-term climate change may be so dominant that they blur or even reverse the apparent direct relationship between climate change and extinction. Here we evaluate how observed genus-level extinctions of arthropods, bivalves, cnidarians, echinoderms, foraminifera, gastropods, mammals and reptiles in the geological past can be predicted from the interaction of long-term temperature trends with short-term climate change. We compare synergistic palaeoclimate interaction (a short-term change on top of a long-term trend in the same direction) to antagonistic palaeoclimate interaction such as long-term cooling followed by short-term warming. Synergistic palaeoclimate interaction increases extinction risk by up to 40%. The memory of palaeoclimate interaction including the climate history experienced by ancestral lineages can be up to 60 Myr long. The effect size of palaeoclimate interaction is similar to other key factors such as geographic range, abundance or clade membership. Insights arising from this previously unknown driver of extinction risk might attenuate recent predictions of climate-change-induced biodiversity loss.
CRIS-Team WoS Importer:2021-02-12